(untitled) (Revista de Ciências Agroveterinárias, 2012)
Brazil is a large milk producer with approximately 21.5 billion liters produced every year. In order to maintain quality, many tests are performed, such as of its stability when mixed with alcohol. Samples are considered positive when there is casein precipitation. Positive milk is discarded by the Brazilian dairy industry on the basis that this product is unstable during thermal milk processing. However, it is known that this milk has nutritional characteristics very similar to the regular milk with slight differences in fat content and it could be used to minimize hunger in the world. There are many controversies about this issue, but it can be said that such a simple analysis is by far the best way to verify milk quality. Alternative uses for this product considered positive should be proposed to minimize economical losses and environmental damage. The objective of this work was to compare the results already published in the literature and to propose alternative uses for alcohol positive milk.